Sweet wormwood: wonderful medicinal plant - Das, Manish; Jat, R S; Rana, V S (Indian Horticulture, 2019)
Sweet wormwood is currently the only source of artemisinin in the world but its crop has undergone a relatively short period of genetic improvement and yields are very low, making it expensive and sometimes unprofitable to produce. The World Health Organisation recommends artemisinin combination therapies (ACTs) for treating malaria. Demand for ACTs is escalating, yet, there is growing concern that existing supply chain will be unable to produce consistent, affordable and high quality artemisinin in quantities that will soon be required. Acreage under sweet wormwood is varying from year to year, raising fears of shortages. Although new approaches to artemisinin production are being developed, it will continue to be essential source to supplies for foreseeable future. Systematic study should be taken up to address the concerns of creating improved new robust varieties as well as cultivation practices and extraction technologies of Sweet wormwood with higher artemisinin output.